Հովսեփ Օրբելու 1916 թ. ուսումնասիրությունները Վանում - Հմայակյան, Սիմոն
Аn idea of archaeological expedition in Van started up in academy of Sciences of Saint Petersburg in 1914, when materials collected there by H. А. Оrbeli in 1911-1912 had been studied. Тhe expedition was ready to start the project in 1915, but the war, which broke out suddenly, hindered the investigation. Nevertheless, H. A. Orbeli and N. Ya. Marr conducted the expedition in Western Armenia during the wartime. It is noteworthy, that three members of expedition were armenians, and earlier S.V. Ter-Avetisyan was delegated to Western Armenia for the record of historical monuments. In 1916 the project was continued by N. Marr and P. N. Makintsyan. the ethnographical data was collected by A.A. Miller. Идея об отправлении археологической экспедиции в ван возникла в академии наук Санкт-Петербурга еще в 1914 г., когда были изучены собранные там в 1911-1912 гг. иосифом орбели материалы. Экспедиция уже была готова пуститься в путь в 1915 г., однако вспыхнувшая война стала тому препятствием. И.А. Орбели и Н. Я. Марр посчитали делом чести начать раскопки в западной армении именно во время войны, невзирая на обстоятельства. Примечательно, что трое членов экспедиции были армянами, а ранее в западную армению был командирован С. В. Тер-Аветисян для учета исторических памятников. В 1916 г. это дело было продолжено Н.Я. Марром и П.Н. Макинцяном. Сбор этнографических материалов был осуществлен А.А. Миллером.
Keywords: Հնագիտություն